-4(6y-8)-y=-4(y-3)

Simple and best practice solution for -4(6y-8)-y=-4(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6y-8)-y=-4(y-3) equation:


Simplifying
-4(6y + -8) + -1y = -4(y + -3)

Reorder the terms:
-4(-8 + 6y) + -1y = -4(y + -3)
(-8 * -4 + 6y * -4) + -1y = -4(y + -3)
(32 + -24y) + -1y = -4(y + -3)

Combine like terms: -24y + -1y = -25y
32 + -25y = -4(y + -3)

Reorder the terms:
32 + -25y = -4(-3 + y)
32 + -25y = (-3 * -4 + y * -4)
32 + -25y = (12 + -4y)

Solving
32 + -25y = 12 + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
32 + -25y + 4y = 12 + -4y + 4y

Combine like terms: -25y + 4y = -21y
32 + -21y = 12 + -4y + 4y

Combine like terms: -4y + 4y = 0
32 + -21y = 12 + 0
32 + -21y = 12

Add '-32' to each side of the equation.
32 + -32 + -21y = 12 + -32

Combine like terms: 32 + -32 = 0
0 + -21y = 12 + -32
-21y = 12 + -32

Combine like terms: 12 + -32 = -20
-21y = -20

Divide each side by '-21'.
y = 0.9523809524

Simplifying
y = 0.9523809524

See similar equations:

| -[3x+(3x+9)]=9-(4x+3) | | X-2+x-3+123=180 | | 2y+12=21 | | 44=-4v | | 3(x+1)+4=22 | | .4(x+.7)=.6x-4.2 | | 9-6y^2= | | 8+4p=10p-4 | | 10-4x=-32 | | 9k+4=22 | | 6-(b+2)= | | y-2=6x | | 25m+22=9m | | 6(2/3)-4(3/4)=1 | | -12=r+12 | | 7x-1=5+4x | | -5.5n+0.56=1.64 | | 2(x+9)=2-(x-9) | | 5(z-18)-30=6 | | 180-x=46(90-x) | | 39=84w+39 | | 3(f-8)=33 | | 2x-5=x+9+5 | | -5+4(3-n)= | | y=ln(5x^3) | | 8d^2+30d+25=0 | | -3x+-10x-14=-12 | | (3n+6)(n-2)=0 | | 5-6=3.75 | | 2.8+7=4.8+89 | | 3x=9x-10 | | 42=3y+9 |

Equations solver categories